Antifungal Activities of Sweet Basil (Ocimum basilicum L.) Aqueous Extract Against Sclerotium rolfsii, Causal Agent of Damping-Off on Tomato Seedling - Cipto Nugroho; Eka Mirnia; Christian Joseph R. Cumagun (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2019)
The study aims to evaluate the effectiveness of sweet basil aqueous extract against Sclerotium rolfsii in-vitro and damping-off on tomato seedling in-vivo. The sweet basil leaves were obtained from a commercial market in Los Banos, Philippines. The leaves were rinsed by water and then air dried. The dried leaves were ground using a domestic blender and 10 grams of this material was extracted using 100 ml of sterile distilled water (1:10 w/v) and 0.01 ml absolute methanol. The mixture was kept for 48 hours at room temperature. The solution was strained by a Whatman filter paper No. 1, then the extract was stored at 4°C. The effectiveness of sweet basil extract was determined in-vitro by measuring the mycelial growth inhibition of S.rolfsii and in-vivo by the percentage of disease incidence on tomato seedlings. The result showed that sweet basil extract was effective to inhibit the mycelial growth (33.35%). However, the effectiveness of water extract of sweet basil was considered ineffective for reducing disease incidence on the inoculated tomato seedlings, i.e. 46.67%-60%, similar to benomyl after the inoculation. Further investigation is needed to find out an effective formula of O. basilicum leaf extract which is stable and prolonged persistence for controlling S. rolfsii.